2021
DOI: 10.3390/min11010051
|View full text |Cite
|
Sign up to set email alerts
|

Controls of Distinct Mineral Compositions on Pore Structure in Over-Mature Shales: A Case Study of Lower Cambrian Niutitang Shales in South China

Abstract: Investigating the impacts of rock composition on pore structure is of great significance to understand shale gas occurrence and gas accumulation mechanism. Shale samples from over-mature Niutitang formation of Lower Cambrian in south China were measured by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), low pressure N2 and CO2 adsorption to elucidate the controls of distinct mineral composition on pore development. Two distinct lithofacies, namely siliceous shale and argillaceous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Besides, quartz and feldspar, as the most important brittle minerals, are principal factors affecting the fracability of the shale. Affected by tectonic stress in the later stage, a complex fracture network system might be formed, increasing the seepage capacity of shale gas. Organic matter and clay minerals present higher specific areas and strong capability of shale gas adsorption for their small constituent molecules, which can provide more adsorption potentials for the gas and increase the adsorption capacity of shale gas, principally affecting the content of adsorbed gas of the shale. The difference in mineral composition is a critical factor affecting shale quality according to the analysis of the difference in shale gas adsorption capacity of different clay minerals and water contents and analysis concerning the influence of mineral composition on different shale levels gas contents. …”
Section: Introductionmentioning
confidence: 99%
“…Besides, quartz and feldspar, as the most important brittle minerals, are principal factors affecting the fracability of the shale. Affected by tectonic stress in the later stage, a complex fracture network system might be formed, increasing the seepage capacity of shale gas. Organic matter and clay minerals present higher specific areas and strong capability of shale gas adsorption for their small constituent molecules, which can provide more adsorption potentials for the gas and increase the adsorption capacity of shale gas, principally affecting the content of adsorbed gas of the shale. The difference in mineral composition is a critical factor affecting shale quality according to the analysis of the difference in shale gas adsorption capacity of different clay minerals and water contents and analysis concerning the influence of mineral composition on different shale levels gas contents. …”
Section: Introductionmentioning
confidence: 99%
“…The intergranular pores and organic pores are developed in Niutitang Formation siliceous shale (Niu et al 2021), while Wang et al (2020a, b) found that the organic pores are rarely developed in the Niutitang Formation shale. For the argillaceous shale in the Niutitang Formation, the intergranular pores are less developed, and the cleavage-sheet intraparticle pores are developed in the clay minerals (Niu et al 2021). The content of TOC (< 6.5%) and quartz favor the development of pores for the siliceous shale, especially that for the micropores (Wang et al 2016b, c;Niu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For the Niutitang Formation shale in Guizhou, the content of quartz is also high, and the quartz comes from both continental detrital quartz and biogenetic quartz (Sun et al 2021). The intergranular pores and organic pores are developed in Niutitang Formation siliceous shale (Niu et al 2021), while Wang et al (2020a, b) found that the organic pores are rarely developed in the Niutitang Formation shale. For the argillaceous shale in the Niutitang Formation, the intergranular pores are less developed, and the cleavage-sheet intraparticle pores are developed in the clay minerals (Niu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations